THE IMPACT OF ARTIFICIAL INTELLIGENCE ON FINANCIAL LITERACY - Lakshmi, Y (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Artificial Intelligence (AI) has emerged as a transformative force within the financial sector, altering not only the mechanisms of finance but also the foundational elements of financial literacy. As AI continues to evolve, it reshapes how individuals interact with financial information, making complex financial concepts more accessible while simultaneously introducing new challenges. This paper provides a comprehensive examination of AI’s influence on financial literacy, exploring the multifaceted ways in which AI-driven technologies are democratizing financial knowledge, enhancing personal financial management, and posing potential risks.